Unravelling the confusions: Defining concepts to record archaeological and historical evidence for knitting - Malcolm-Davies, Jane; Gilbert, Ruth; Lervad, Susanne (Archaeological Textiles Review, 2018)
Evidence for the development of knitting as a craft and industry is not as readily available as it is for weaving. The reasons for this include the relative scarcity of the archaeological and historical material, its inaccessibility due to incomplete or inaccurate cataloguing, and the lack of agreed terminology for a scholarly discussion. This paper proposes a vocabulary based on English terminology used in textile analysis, in craftwork and in the mechanised knitting industry today. A recording protocol is required to provide reliable descriptive detail for those who cannot view the items for themselves and to off er a sound foundation upon which later observers can build with further insights. This paper aims at a protocol for recording knitted items which may be used as a guideline by experts and non-experts in textile analysis of knitwork. It cautions against deductions as to methods of construction without credible evidence and calls for more discussion of appropriate terms in English and other languages.